2024
DOI: 10.7150/thno.85917
|View full text |Cite
|
Sign up to set email alerts
|

Engineered bacterial outer membrane vesicles: a versatile bacteria-based weapon against gastrointestinal tumors

Keshuang Zheng,
Yongpu Feng,
Lei Li
et al.

Abstract: Outer membrane vesicles (OMVs) are nanoscale lipid bilayer structures released by gram-negative bacteria. They share membrane composition and properties with their originating cells, making them adept at traversing cellular barriers. These OMVs have demonstrated exceptional membrane stability, immunogenicity, safety, penetration, and tumor-targeting properties, which have been leveraged in developing vaccines and drug delivery systems. Recent research efforts have focused on engineering OMVs to increase produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…As described in the section below, a different approach could involve engineering to alter the intrinsic properties of bEVs. This area of research is far more advanced in the field of mammalian EVs and synthetic nanoparticles [ 123 126 ], which could provide significant insight for bEV applications as well. For example, mammalian EV circulating time was significantly increased when they were engineered to express the “don't-eat-me” signal, CD47, which inhibits phagocytosis by macrophages upon ligation with its receptor, SIRPα [ 127 ].…”
Section: Microbiome Revelations Spur Interest In Bugs-as-drugs For Ca...mentioning
confidence: 99%
“…As described in the section below, a different approach could involve engineering to alter the intrinsic properties of bEVs. This area of research is far more advanced in the field of mammalian EVs and synthetic nanoparticles [ 123 126 ], which could provide significant insight for bEV applications as well. For example, mammalian EV circulating time was significantly increased when they were engineered to express the “don't-eat-me” signal, CD47, which inhibits phagocytosis by macrophages upon ligation with its receptor, SIRPα [ 127 ].…”
Section: Microbiome Revelations Spur Interest In Bugs-as-drugs For Ca...mentioning
confidence: 99%
“…In recent years, studies have shown that gram-negative bacteria can naturally release outer membrane vesicles (OMVs), which comprises of lipopolysaccharides (LPS), outer membrane proteins, periplasmic proteins, and phospholipids and can serve as carriers for various substances such as toxins, metabolites, enzymes, virulence factors, and genetic material (DNA and RNA) [ 11 13 ]. Unlike attenuated bacteria, OMVs are considered safer and can effectively stimulate the immune system by delivering key immunogens from their parent bacteria [ 13 15 ]. Genetic engineering techniques have shown that the construction of recombinant OMVs improves target precision through surface protein and carries exogenous proteins for improved immunogenicity [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%